Regulatory Challenges in Wastewater Management and its Impacts on Environmental Sustainability - Maskun, Maskun; Kamaruddin, Hanim; Khalid, Rasyikah Md; Anugerah, Muhammad; Wiranti, Wiranti; Bachril, Siti Nurhaliza (Faculty of Law, Hasanuddin University, 2024)
Before the enactment of the Job Creation Law, liquid waste disposal was governed by a specific permit system. However, with the introduction of the Job Creation Law, this system transitioned to requiring businesses to obtain technical approvals to comply with wastewater quality standards. Challenges have emerged, particularly improper practices that fail to align with ethical environmental principles. This research critically examines Indonesia's legislative framework for liquid waste management, focusing on its implementation and impact under the Job Creation Law, with a specific emphasis on environmental sustainability. A significant finding highlights persistent issues in managing household and laundry wastewater, which remain inadequately addressed under current regulations. Such gaps undermine environmental ethics, both anthropocentrism and ecocentrism. This paper advocates for synchronized regulations and comprehensive guidelines to mitigate adverse effects on environmental sustainability, ensuring stronger legal protections for Indonesian society.